2022
DOI: 10.1530/vb-21-0018
|View full text |Cite
|
Sign up to set email alerts
|

Progerin mislocalizes myocardin-related transcription factor in Hutchinson–Guilford Progeria syndrome

Abstract: Hutchinson-Guilford Progeria Syndrome (HGPS) is a rare genetic disease of premature aging and early death due to cardiovascular disease. The arteries of HGPS children and mice are pathologically stiff, and HGPS mice also display reduced arterial contractility. We recently showed that reduced contractility is an early event in HGPS and linked to an aberrantly low expression of smooth muscle myosin-heavy chain (SM-MHC). Here, we have explored the basis for reduced SM-MHC abundance and asked whether it is a direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
2
0
Order By: Relevance
“…Skin tissue sections from patients with HGPS have shown that progerin accumulates primarily in the nuclei of vascular cells, suggesting that its accumulation has a direct association with vascular diseases in progeria [19]. Similarly, several reports have suggested that progerin in vascular muscles could accelerate atherosclerosis by inducing endoplasmic reticulum (ER) stress, DNA damage, wound healing impairment, mislocalization of a myocardinrelated transcription factor, and replication stress [77][78][79][80][81]. Recently, Hamczyk et al (2018) produced the first mouse model (Apoe -/-Lmna LCS/LCS SM22αCre) with progerin-induced atherosclerosis acceleration expressing progerin specifically in VSMCs and demonstrated that restricting progerin expression to VSMCs is sufficient to accelerate atherosclerosis, trigger plaque vulnerability, and reduce lifespan [66].…”
Section: B Systemic Effect Of Progerin or Effect Of Progerin On Tissuesmentioning
confidence: 99%
“…Skin tissue sections from patients with HGPS have shown that progerin accumulates primarily in the nuclei of vascular cells, suggesting that its accumulation has a direct association with vascular diseases in progeria [19]. Similarly, several reports have suggested that progerin in vascular muscles could accelerate atherosclerosis by inducing endoplasmic reticulum (ER) stress, DNA damage, wound healing impairment, mislocalization of a myocardinrelated transcription factor, and replication stress [77][78][79][80][81]. Recently, Hamczyk et al (2018) produced the first mouse model (Apoe -/-Lmna LCS/LCS SM22αCre) with progerin-induced atherosclerosis acceleration expressing progerin specifically in VSMCs and demonstrated that restricting progerin expression to VSMCs is sufficient to accelerate atherosclerosis, trigger plaque vulnerability, and reduce lifespan [66].…”
Section: B Systemic Effect Of Progerin or Effect Of Progerin On Tissuesmentioning
confidence: 99%